KAJIAN GEOTEKNIK STRUKTUR BAWAH BANGUNAN RUANG GENSET DI PELABUHAN TANJUNG EMAS SEMARANG - Anggoro Setyo Pratomo; Dwi Purnamajati; Indrastono Dwi Atmanto; Himawan Indarto (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2015)
One of Tanjung Emas Port’s primary facility is container terminal yard used as center of container handling. The traffic of goods increase year by year. For increasing performance it needs center of generator room for e-RTG (Electrified Rubber Tyred Gantry Cranes) and CC (Container Crane). Therefore it is needed to build Generator Room at Container Terminal so that the activity of unloading and loading is getting easier. Before build Generator Room at Container Terminal, first we evaluated geotechnic and the structure of building. The part of upper structure design uses SRPMK with Strong Coloumn Weak Beam method, for foundation consists of pilecap with concrete pile until depth 20 m. From the result of analysis geotechnic and building structure can hold the load of the building. The consolidation settlement at Container Terminal Semarang area is 8,17 cm with time’s consolidation is 17 mounths 16 days, so it must be compacted to increase its density.